Becoming a youth activist in the internet age: a case study on social media activism and identity development. Issue 4 (21st April 2017) - Fullam, Jordan
Abstract: This paper draws on a case study of one youth activist, and explores connections between social media activism, identity development, and critical education. Justin Rodriguez, a 17-year-old high school student in Newark, New Jersey, leveraged social media and texting as organizing tools and garnered support for a school walkout to protest education budget cuts. Drawing on the Listening Guide interview method and Justin's narrative of his experiences, the study explores the question: Does social media activism have implications for how we understand the development of youth activist identities? The findings suggest Justin's development as a youth activist was mediated, not produced, by social media activism; and Justin developed as a youth activist through various forms of interaction that included social media and face-to-face relationships. The paper also explores the supports provided by adult mentors that were important in Justin's development as an activist, including education for critical consciousness and opportunities for Justin to participate in civic venues.